Response Modifiers: Tweaking the Immune Response Against Influenza A Virus - Elbahesh, Husni; Gerlach, Thomas; Saletti, Giulietta; Rimmelzwaan, Guus F. (Frontiers in Immunology, 2019)
Despite causing pandemics and yearly epidemics that result in significant morbidity and mortality, our arsenal of options to treat influenza A virus (IAV) infections remains limited and is challenged by the virus itself. While vaccination is the preferred intervention strategy against influenza, its efficacy is reduced in the elderly and infants who are most susceptible to severe and/or fatal infections. In addition, antigenic variation of IAV complicates the production of efficacious vaccines. Similarly, effectiveness of currently used antiviral drugs is jeopardized by the development of resistance to these drugs. Like many viruses, IAV is reliant on host factors and signaling-pathways for their replication, which could potentially offer alternative options to treat infections. While host-factors have long been recognized as attractive therapeutic candidates against other viruses, only recently they have been targeted for development as IAV antivirals. Future strategies to combat IAV infections will most likely include approaches that alter host-virus interactions on the one hand or dampen harmful host immune responses on the other, with the use of biological response modifiers (BRMs). In principle, BRMs are biologically active agents including antibodies, small peptides and/or other (small) molecules that can influence the immune response. BRMs are already being used in the clinic to treat malignancies and autoimmune diseases. Repurposing such agents would allow for accelerated use against severe and potentially fatal IAV infections. In this review, we will address the potential therapeutic use of different BRM classes to modulate the immune response induced after IAV infections.